Building Pillars of Sustainability: An Empirical Investigation - Batham, Triveni (Prabandhan: Indian Journal of Management, 2013)
In the present parlance, sustainability is the requirement. Humankind is using natural resources at a faster rate than they are being replaced. If this continues, future generations will not have the resources they need for their development. Sustainable development is about meeting the needs of the society while living within the planet's ecological limits and without jeopardizing the ability of future generations to meet their needs. Social responsibility is closely linked to sustainable development. Corporate Social Responsibility is an entry point for understanding sustainable development issues and responding to them in a firm's business strategy. Keeping in mind the objectivity of the article, the paper describes the conceptual framework of sustainable development and its three pillars. The next section discusses the relationship between sustainable development and corporate social responsibility in the context of developing economies. For the empirical analysis, the hypotheses were formulated to study the relationship between the average market price of the companies and the environmental performance and expenditure on CSR.